2009
DOI: 10.1510/icvts.2009.206607
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension in rheumatic mitral stenosis: does it affect right ventricular function and outcome after mitral valve replacement?☆

Abstract: Right ventricular function affects the outcome in valvular heart disease but less is known about the relation between indices of dysfunction and outcome. Seventy patients undergoing mitral valve replacement between April 2007 and April 2008 for predominant rheumatic mitral stenosis were included in the study. Two groups were formed based on right ventricular systolic pressure (RVSP), 41 mmHg (group II, n=54). Right ventricle (RV) function indices were studied by echocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Mittal and Goozar 15 found significantly impaired RV systolic function in 22 cases of isolated rheumatic MS and did not find any relationship between parameters of RV systolic function and PASP and the authors attributed the impairment of RV systolic function to myocardial involvement of the rheumatic process. RV systolic dysfunction has also been reported in all cases of rheumatic MS regardless of pulmonary artery pressure 16 and long term follow up of cases with MS, revealed evidence for progressive right heart disease independent of MS severity. 9 Inci et al 17 evaluated RV systolic function before, immediately after, and at 3 months and 1 year after percutaneous balloon mitral valvuloplasty (PBMV) by conventional and TDI imaging methods and observed no improvement in the RV systolic function despite the improved hemodynamic status and attributed their findings to irreversible myocardial damage due to rheumatic pathology or long-lasting hemodynamic burden.…”
Section: Discussionmentioning
confidence: 76%
“…Mittal and Goozar 15 found significantly impaired RV systolic function in 22 cases of isolated rheumatic MS and did not find any relationship between parameters of RV systolic function and PASP and the authors attributed the impairment of RV systolic function to myocardial involvement of the rheumatic process. RV systolic dysfunction has also been reported in all cases of rheumatic MS regardless of pulmonary artery pressure 16 and long term follow up of cases with MS, revealed evidence for progressive right heart disease independent of MS severity. 9 Inci et al 17 evaluated RV systolic function before, immediately after, and at 3 months and 1 year after percutaneous balloon mitral valvuloplasty (PBMV) by conventional and TDI imaging methods and observed no improvement in the RV systolic function despite the improved hemodynamic status and attributed their findings to irreversible myocardial damage due to rheumatic pathology or long-lasting hemodynamic burden.…”
Section: Discussionmentioning
confidence: 76%
“…13,14 It strongly expresses valve disease severity and conveys adverse effects on functional status, exercise tolerance, and prognosis. 15,16 However, pulmonary pressure may not be uniquely determined by the stenotic lesion itself but by a combination of hemodynamic parameters. 17,18 Several factors may contribute to clinical presentation and outcome in MS. Leftheart compliance plays a crucial role in the occurrence of pulmonary hypertension and symptoms.…”
mentioning
confidence: 99%
“…4, 32 RV dysfunction is not a simple expression of elevated pulmonary artery pressure. 33 Pande et al 4 showed that RV dysfunction was observed in all cases of rheumatic MS regardless of SPAP. Similarly, Sagie et al 34 demonstrated that right heart disease can progress independent of MV area.…”
Section: Discussionmentioning
confidence: 99%